Prevalence of Gait Features in Healthy Adolescents and Adults - Kim, Nak Tscheol; Moon, Seung Jun; Park, Moon Seok; Lee, Kyoung Min; Choi, Kug Jin; Choi, Woo Young; Sung, Ki Hyuk (Korean Journal of Legal Medicine, 2021)
Forensic gait analysis is the identification of individuals by their gait style and walking characteristics. This study aimed to examine the prevalence of gait patterns in healthy adolescents and adults. Five hundred healthy participants (mean age, 36.9 years) were enrolled and divided into four age groups: 13-20, 21-35, 36-50, and ≥51 years. The gait of the participants was recorded in a gait analysis laboratory. Five specialists experienced in gait analysis selected several gait features. The prevalence of out-toe, in-toe, planovalgus, and turtleneck was 25.0%, 1.6%, 6.8%, and 4.2%, respectively. The prevalence of genu varum (10.4%) was higher than that of genu valgum (5.6%). Genu valgum and hindfoot valgus were more common in younger than in older subjects (P=0.018 and P=0.029, respectively). Genu varum was more prevalent in older subjects (P<0.001). The prevalence of out-toe was higher in males (P<0.001), whereas the in-toe and genu valgum were more common in females than in males (P=0.027 and P=0.038, respectively). We have documented the prevalence of several gait features in healthy adolescents and adults. These gait features can be used to enhance evidentiary competence in forensic gait analysis and thereby help improve the arrest rate of offenders. KCI Citation Count: 0